Scientific Opinion on applications (EFSA‐GMO‐RX‐GT73) for renewal of the authorisation for continued marketing of existing (1) food and food ingredients produced from oilseed rape GT73; and of (2) feed materials, feed additives and food additives produced from oilseed rape GT73, all under Regulation (EC) No 1829/2003 from Monsanto - EFSA Panel on Genetically Modified Organisms (GMO Panel) (EFSA Journal)
Abstract This scientific opinion reports on an evaluation of a risk assessment for renewal of the authorisation for continued marketing of existing food and feed ingredients, feed materials, feed additives and food additives produced from hybrid oilseed rape GT73. Oilseed rape GT73 has been modified with two genes encoding the CP4 EPSPS and GOX proteins that confer glyphosate tolerance and resistance, respectively. In 2004 the EFSA GMO Panel had issued a scientific opinion on the safety of glyphosate‐tolerant oilseed rape GT73 for import and processing uses. In delivering the present opinion, the EFSA GMO Panel considered the information provided in the applications EFSA‐GMO‐RX‐GT73[8.1.a] and EFSA‐GMO‐RX‐GT73[8.1.b/20.1.b] as well as additional information provided by the applicant and information published in the scientific literature. The new data in the application included bioinformatic analyses using updated databases which confirmed that no relevant similarities exist between the newly expressed proteins and known allergens and toxic proteins. The EFSA GMO Panel reiterates the conclusions of its previous scientific opinion of 2004 that GM oilseed rape GT73 is unlikely to have an adverse effect on human and animal health and on the environment, in the context of its proposed uses. This also applies to the products which are the subject of the present application.